SOCIAL REPRESENTATION ABOUT FEMALE CITIZENSHIP - Gomes Padilha de Souza, Alexsandra; Renata Mendes Barbosa, Josiane; Mirella Gomes Barros, Kátila; Soares do Nascimento, Nayara; Uchôa, Patrícia; Tinôco, Renata; Menezes, Walfrido (Revista Gênero e Interdisciplinaridade, 2024)
This work reflects an excerpt from a Doctoral Thesis carried out at the Federal University of Pernambuco - UFPE, in 2011, where we reflected, among its approaches, the context of social representations about female citizenship. To this end, we used the EVOC software, in search of the central core and the peripheral elements of social representations, developed by Abric (1994). According to Sá (1998), social representations are processes and structures that emerge from practices in force in society and culture in which the process is constantly fed, although they can perpetuate it or contribute to its own transformation, in the general context. By seeking to study citizenship from the perspective of social representation, we sought to understand how it is represented in the ideas, opinions and conceptions of women, in order to provide a vision that can lead to actions capable of leading to ruptures in the medium or long term. The topic was revisited in the current context of 2024, based on a reinterpretation in the classroom. The theory of social representations seeks to understand how subjects construct knowledge about social objects, recognizing that this knowledge, which comes from the sense, is shaped and disseminated in daily social practices, through everyday interactions and communications. In this sense, female citizenship, as an object of analysis, reflects both historical achievements and persistent challenges, highlighting how the perceptions and values ​​attributed to women continue to be shaped by patriarchal and sexist society.